Characterisation of placental and platelet exosome-bound cardiotrophin-1 in cardiomyocyte and endothelial cell function - Mhlomi, V (2017)
Maternal cardiovascular adaptions during pregnancy have been well described and include characteristic changes in cardiac morphology and function. The mechanisms behind these changes remain largely unknown but are tied to the developing feto-placental unit. Extracellular vesicles are membrane-encapsulated particles carrying cargo originating from their parental cells and are critical mediators of intercellular communication. Syncytiotrophoblast extracellular vesicles (STB-EV), comprising of microvesicles and exosomes, are released by the placenta into the maternal circulation throughout pregnancy. We hypothesized that there might be molecules on the STB-EV that had cardiac effects. In this thesis, we characterised the expression of Cardiotrophin 1 (CT-1), a known potent inducer of cardiac hypertrophy and regulator of cardiac physiology, as being present on the human placenta. Importantly, we demonstrated that CT-1 is present on both microvesicles and exosomes, with a greater expression on exosomes. Furthermore, we show that CT-1 is biologically active and can phosphorylate its cognate receptor gp130/LIFR. Moreover, we demonstrate downstream signaling pathways that are mediated by STB-EV, most notably STAT 3 and ERK 1/2. We subsequently conducted a transcriptomic analysis using microarrays to investigate the effects of CT-1 positive STB-EV on cardiomyocytes derived from human induced pluripotent stem cells. This analysis showed significantly upregulated and downregulated genes involved in cardiovascular function. Furthermore, gene networking using Ingenuity Pathway Analysis (IPA) revealed STAT 3 as the most likely mediator of these gene changes. Intriguingly, real-time quantitative PCR validation confirmed the vesicular changes seen in the array but revealed that while some of the gene changes are directly due to CT-1, some are almost certainly due to the cargo within the vesicles. As a corollary to our experimental investigations we also identified, for the first time that CT-1 was present in platelets and platelet extracellular vesicles (PEV). We found in vitro evidence that PEV-bound CT-1 phosphorylated gp130 signaling leading to the activation of STAT 3 and ERK 1/2. Furthermore, we demonstrated that CT-1 positive vesicles protect against cytotoxicity in endothelial cells raising the possibility that this cytokine performs a cellular protective role. This thesis thus reports the first observation of active CT-1 expressed in STB-EV from normal placentae and points to a novel finding that the placenta may well play a role in the orchestration of cardiovascular adaptation in pregnancy. Moreover, our results suggest that the placenta can communicate with the maternal heart. Additionally, it places CT-1 in vesicles as playing a significant role in both cardiomyocyte and vascular biology. Finally, the finding that platelets contain Cardiotrophin-1 positive vesicles suggests that this cytokine may well have a role in cellular protection outside pregnancy.